2019
DOI: 10.1158/1541-7786.mcr-19-0040
|View full text |Cite
|
Sign up to set email alerts
|

The Altered Transcriptome and DNA Methylation Profiles of Docetaxel Resistance in Breast Cancer PDX Models

Abstract: Taxanes are standard therapy in clinical practice for metastatic breast cancer; however, primary or acquired chemoresistance are a common cause of mortality. Breast cancer patient-derived xenografts (PDX) are powerful tools for the study of cancer biology and drug treatment response. Specific DNA methylation patterns have been associated to different breast cancer subtypes but its association with chemoresistance remains unstudied. Aiming to elucidate docetaxel resistance mechanisms, we performed genome-wide D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 53 publications
1
12
0
2
Order By: Relevance
“…These results indicated that DNA methylation patterns were different between the two groups of cells. Moreover, many studies have shown that the methylation patterns of breast cancer resistant cells and sensitive cells are different [20][21][22]. This information also proves the reliability of our research results.…”
Section: Different Dna Methylation Patterns Between Two Types Of Breasupporting
confidence: 86%
“…These results indicated that DNA methylation patterns were different between the two groups of cells. Moreover, many studies have shown that the methylation patterns of breast cancer resistant cells and sensitive cells are different [20][21][22]. This information also proves the reliability of our research results.…”
Section: Different Dna Methylation Patterns Between Two Types Of Breasupporting
confidence: 86%
“…Recent studies have reported the role of epigenetic changes in drug resistance, including DNA methylation [ 31 ], histone modifications [ 16 ], and chromatin accessibility [ 13 ]. We next hypothesized that chromatin accessibility is involved in anlotinib resistance.…”
Section: Resultsmentioning
confidence: 99%
“…An open question remains regarding how accurately these PDXs reproduce the metastatic behavior of the patient's tumor, as well as more general metastatic characteristics associated with breast cancer subtype. Although considerable evidence exists that these PDXs can produce CTCs and generate micro-and macroscopic metastatic lesions within several distant sits in the mouse (41,(43)(44)(45), a full credentialization of the metastatic propensity of this vast tissue resource remains an evolving collective task. Given that ER+ cancers typically exhibit longer latency and a proclivity to metastasize to bone, the development of humanized mouse models in which breast cancer PDXs metastasize to human bone implants has created a highly reliable system to interrogate late-stage metastasis to the bone (46).…”
Section: In Vivo Orthotopic Xenograft Models Of Metastasismentioning
confidence: 99%